PEMBINAAN DAN PENDAMPINGAN KELOMPOK WANITA TANI RUMPUT LAUT DESA KUTUH DALAM PENGEMBANGAN PRODUKSI NUGGET RUMPUT LAUT - Yusasrini, N.L. Ari; Darmayanti, Luh Putu T.; Suter, I.K. (Buletin Udayana Mengabdi; Vol 16 No 1 (2017), 2018)
Women Farmers Group (WFG) Merta Nadhi and Sri Rahayu located in the village Kutuh, Badung regency known to actively develop creative products such as nuggets of processed seaweed. Both WFG were facing the same problems in terms of processing technology of seawed nugget and packaging techniques according to the standard so it has not been able to produce products that can compete in the market. The purpose of this activity was to provide guidance and assistance for WFG in the development process of seaweed nugget production, so as to produce a good product and corresponding ISO standards. The method would be developed to achieve these objectives were (1) provided of facilities and infrastructure that support production activities, (2) provided counseling and training / practice guided about processing technology of seaweed into nugget with different types of flavors (chicken nugget-seaweed, fish nugget - seaweed and shrimp nugget-seaweed) and good packaging techniques to produce a quality product. The results showed that WFG members were excited to follow all stages of activities. WFG of Sri Rahayu and Merta Nadhi also have been able to produce nugget of seaweed with 3 variations of flavor and successfully improve the quality of nuggets, both in terms of taste and appearance package.